Mg-Al hydrotalcites as solid base catalysts for transformation of glucose to fructose - Son, Pham Anh; Canh, Kieu Thanh (Vietnam Journal of Chemistry, 2017)
In this research, Mg-Al hydrotalcite compounds (HTs) are fabricated by constant pH at low supersaturation method. The prepared HTs act as solid base catalysts for the transformation of glucose to fructose in water medium. The activities of catalysts are monitored versus reaction temperature and time to find the optimum conditions. Under 120 oC and 20 min, the best catalyst is HT5 with maximum fructose yield of 16.3 %. The HT5 catalyst is tested for the heterogeneous nature and recyclability. The obtained results show that HT5 is true solid base catalyst. HT5 can be recovered easily and reuse several times with slight decrease in its activity. The deposition of organic residue on the surface of HT5 grains is blamed for the depletion of catalytic activity. In the regeneration process, HT5 undergoes a thermal treatment at 500 oC for 4 h in air to remove completely the contaminations. During that process, HT5 disassociates into MgO and Al2O3 before reconstruction stage in water medium to come back original structure of hydrotalcite. The reconstruction of HT5 can repeat many times proving that hydrotalcites are structure-memory materials. The activity of regenerated HT5 can be comparable to that of fresh catalyst. Keywords. Glucose, fructose, isomerization reaction, hydrotalcite, solid base catalyst